Safety and efficacy of co-trimoxazole for treatment and prevention of Plasmodium falciparum malaria: a systematic review. - Christine Manyando; Eric M Njunju; Umberto D'Alessandro; Jean-Pierre Van Geertruyden (PLoS ONE, 2013)
Introduction Cotrimoxazole (CTX) has been used for half a century. It is inexpensive hence the reason for its almost universal availability and wide clinical spectrum of use. In the last decade, CTX was used for prophylaxis of opportunistic infections in HIV infected people. It also had an impact on the malaria risk in this specific group. Objective We performed a systematic review to explore the efficacy and safety of CTX used for P.falciparum malaria treatment and prophylaxis. Result CTX is safe and efficacious against malaria. Up to 75% of the safety concerns relate to skin reactions and this increases in HIV/AIDs patients. In different study areas, in HIV negative individuals, CTX used as malaria treatment cleared 56%-97% of the malaria infections, reduced fever and improved anaemia. CTX prophylaxis reduces the incidence of clinical malaria in HIV-1 infected individuals from 46%-97%. In HIV negative non pregnant participants, CTX prophylaxis had 39.5%-99.5% protective efficacy against clinical malaria. The lowest figures were observed in zones of high sulfadoxine-pyrimethamine resistance. There were no data reported on CTX prophylaxis in HIV negative pregnant women. Conclusion CTX is safe and still efficacious for the treatment of P.falciparum malaria in non-pregnant adults and children irrespective of HIV status and antifolate resistance profiles. There is need to explore its effect in pregnant women, irrespective of HIV status. CTX prophylaxis in HIV infected individuals protects against malaria and CTX may have a role for malaria prophylaxis in specific HIV negative target groups.